Three-dimensional auditory localization in the echolocating bat. (December 2016) - Wohlgemuth, Melville J; Luo, Jinhong; Moss, Cynthia F
Highlights: Echolocating bats use acoustic information to build a 3D representation of space. Auditory selectivity to direction and distance are integrated in 3D space neurons. Auditory localization involves interconnected circuits in the auditory pathway. Range-tuned neurons show dynamic responses that change with stimulus context. Abstract : Echolocating bats exhibit accurate three-dimensional (3D) auditory localization to avoid obstacles and intercept prey. The bat achieves high spatial resolution through a biological sonar system. Key features of the bat's sonar system are (1) high frequency, directional echolocation signals; (2) high frequency hearing; (3) mobile ears; and (4) measurement of distance from the time delay between sonar emission and echo reception. The bat's sonar receiver is a standard mammalian auditory system that computes azimuth from inter-aural differences and elevation from spectral filtering by the ear [1–3 ]. Target range is computed from echo arrival time [4, 5 ], and the bat auditory system contains neurons that show echo delay-tuned responses to pulse-echo pairs [6 ]. Ultimately, information about sound source azimuth, elevation and range converge to create a unified representation of 3D space.